A note on a new constitutive model for rubber-like solids. (October 2021) - Bustamante, R.
Abstract: A new constitutive equation is proposed for rubber, based on expressing the Cauchy stress as a function of the Hencky strain tensor. The model is used for isotropic bodies considering the classical invariants of Rivlin and Spencer. The predictions for the extension and compression of a cylinder, and the inflation of a hollow sphere, are compared with the predictions of the constitutive equation for rubber by Ogden. Highlights: A new model is presented for rubber. A comparison with the Ogden's model is provided. The behaviour of a hollow sphere is studied. obtained.